EFEKTIVITAS KONSELING KELOMPOK BERBASIS REBT UNTUK MENINGKATKAN ADVERSITY QUOTIENT PADA SISWA - Adinda Jovita Emmanuela Ragil; Yashinta Sari Pratiwi; Dwi Sona; Nuril Hidayanti (IKIP Siliwangi, 2026)
This study was conducted based on data obtained from a preliminary study involving eleventh-grade students at SMA Negeri 2 Bontang, which indicated a low level of adversity quotient. The findings revealed that students tended to give up easily when facing difficulties in learning or social situations, felt unable to control challenging circumstances, were reluctant to take responsibility for their problems, and experienced a decline in learning motivation when confronted with academic pressure or failure. The research employed a quantitative experimental design, specifically a nonequivalent control group design. The population consisted of 30 eleventh-grade students identified as having a low adversity quotient, with a sample of six students selected based on purposive non-probability sampling techniques. The sample was divided into two groups: an experimental group and a control group. The group counseling sessions were conducted five times, applying the Rational Emotive Behavior Therapy (REBT) approach for the experimental group and conventional group counseling for the control group. The pre-test scores showed an average of 31.66 for the experimental group and 29.33 for the control group. After the counseling sessions, the post-test average scores increased to 72.33 for the experimental group and 63.33 for the control group, indicating an average score increase of 40.67 and 34.00, respectively. The results demonstrated a significant improvement in students’ adversity quotient. Therefore, it can be concluded that REBT-based group counseling is effective in enhancing the adversity quotient of eleventh-grade students at SMA Negeri 2 Bontang in the 2024/2025 academic year.